Export Support System of the Republic of Korea and Applicable Experiences for Mongolia - Myagmar Dashdavaa (Олон улс судлал)
Government organizations play a pivotal role in fostering export development. We need to create efficient organizational system for economic diversification. Within this context, I examine the structure and functions of organizations headed by the Ministry of Trade, Energy, and Industry of the Republic of Korea. This ministry plans export support initiatives, which are then executed through its affiliated agencies and other governmental and nongovernmental organizations. The interconnected and well-coordinated export support system, which has evolved since the 1960s, continues to operate with notable efficiency.